MENGUKUR KEBERHASILAN PENERAPAN SISTEM INFORMASI AKADEMIK DENGAN MODEL KESUKSESAN DELON AND MCLEAN - Nur Nawaningtyas Pusparini; Asrul Sani (Universitas Methodist Indonesia, 2020)
Academic information systems are designed to manage academic-related data using computer technology. The quality of the information system helps provide satisfaction for the organization and increases competitiveness, providing added value to STMIK Widuri. To measure the success of a system can apply the success model of Delone and McLean.By testing the system using DeLone and McLean it is known that the STMIK Widuri academic information system as a whole has a good quality system and scores 81.63%.